Perceptions And Behaviors Of International Tourists Toward Cultural Authenticity In Mepantigan - Tasya Winston; Kresensia Yufarita Anderi; Ni Luh Putu Eka Wahyuni; Ni Made Ayu Natih Widhiarini (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2026)
Cultural tourism in Bali faces increasing challenges of commodification that risk reducing local traditions to market-oriented attractions. This article examines international tourists’ perceptions and behaviors toward cultural authenticity in Mepantigan, a traditional Balinese martial art that integrates physical interaction, philosophical values, and cultural expression. The study aims to understand how participatory cultural activities shape tourists’ interpretations of authenticity. A descriptive qualitative approach with a case study design was employed, using participatory observation, semi-structured interviews and documentation. The collected data were analyzed thematically to identify patterns of perception and behavior. The findings reveal that direct involvement in Mepantigan fosters a strong sense of cultural authenticity, as tourists experience local values through embodied participation rather than passive observation. The interaction between physical engagement, philosophical explanation, and reflective experience enhances tourists’ appreciation of Balinese culture. This study contributes to cultural tourism research by demonstrating that authenticity is dynamically constructed through participatory experiences, offering practical insights for managing sustainable and meaningful cultural tourism in Bali.